Development of Scientific Skills in Early Childhood. A Case Study Among Kindergarten Children at Institucion Educativa Villa Flora, Medellín - Del Valle Grisales, Liliana María; Mejía Aristizábal, Luz Stella (Íkala, Revista de Lenguaje y Cultura, 2016)
This text is an outcome of a research work whose main goal was to analyze the development of scientific skills among students in kindergarten at Institución Educativa Villa Flora (Villa Flora Elementary school) in the city of Medellín, through ludic-pedagogical project; My Body. In this study, 4 girls and 4 boys, between 5 and 6 years old, took part. The research is enrolled in the qualitative paradigm and the methodological strategic selected was case study. Nonparticipatory observation, audio and video recordings, as well as a performance grid format were used to analyze the results. It was found that students use, in a flexible and spontaneous way, their abilities and knowledge in their daily actions and social interactions, that “Know-how”, with themselves, with others and with their environment. Besides, when they make inferences and formulate hypotheses to solve a simple problem, it is transformed into achievements aimed at developing their skills and scientific training.